Patients’ awareness regarding the quality of their oral hygiene: development and validation of a new measurement instrument - Eidenhardt, Zdenka; Busse, Sebastian; Margraf-Stiksrud, Jutta; Deinzer, Renate; Justus Liebig University Giessen (My University, 2022)
Background: The present research aimed to develop and validate a standardised survey instrument for the assessment of patients’ awareness of the quality of their oral hygiene performance. Methods: A digital questionnaire was developed that assesses both patients’ naïve self-perceptions of oral cleanliness (SPOCn) after tooth brushing and patients’ perceptions after being informed how oral cleanliness may be captured in dentistry (SPOCd). Three studies (N = 56 adults, N = 66 adolescents and one of their parents, N = 24 university students) assessed the instrument’s feasibility (patient reports), reliability (internal consistency), validity (correlation with other constructs; sensitivity to manipulation of actual tooth brushing), and the correlation with actual oral cleanliness after tooth brushing. Results: All study groups accepted the questionnaire well; average answering times were less than 5 min. Cronbach’s α exceeds 0.90; correlational analyses support the discriminant validity regarding oral hygiene related self-efficacy expectations and stages of change; manipulation of oral hygiene behaviour results in the expected changes of SPOC scores. Patients’ SPOC correlate only moderately with actual oral cleanliness. The comparison between SPOCd scores and actual oral cleanliness indicate that they considerably overestimate their oral hygiene performance. Conclusions: The SPOC questionnaire is an easy-to-use, well-accepted, reliable and valid instrument for the assessment of patients’ awareness of the quality of their oral hygiene for research and clinical purposes. The results of the questionnaire may help to reveal unrealistic self-perceptions of patients regarding their oral hygiene. It can raise their awareness of the need to improve their skills and/or efforts in this regard.
Keywords: Oral hygiene; Tooth brushing; Dental plaque; Dental health surveys; Health education; Health behavior; Periodontal disease; ddc:150